Aktivitas Antibakteri Ekstrak Biji Anggur (Vitis vinifera L.) terhadap Enterococcus faecalis - Vera Nanda, Elsa; Hamida, Fathin; Puspita, Dian; Syafriana, Vilya (Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
Background: Grape seeds are one part of the grape plant known to have antibacterial properties because they contain secondary metabolite compounds such as tannins and flavonoids. Previous studies have shown that grape seed extract has antibacterial activity against Streptococcus pyogenes, Streptococcus mutans, Propionibacterium acnes, and Staphylococcus epidermidis. However, testing for Enterococcus faecalis from 70% ethanol extract and n-hexane has not been found. This study aims to determine the antibacterial activity of n-hexane and 70% ethanol extract from grape seeds against E. faecalis bacteria. Methods: Extraction was carried out using the maceration method using two solvents: n-hexane and 70% ethanol. The antibacterial activity test used the disc diffusion method to determine the Diameter Inhibitory Power (DDH) value at extract concentrations of 5%, 10%, 20%, and 40%. Results: The results obtained showed that grape seed extract had antibacterial activity against E. faecalis, with the DDH value of n-hexane extract respectively being 9.70 mm, 10.36mm, 10.55mm, and 11.31 mm at concentrations of 5%, 10%, 20%, and 40%. The DDH value of the 70% ethanol extract was 11.20 mm, 12.34mm, 13.63mm, and 15.49 mm at concentrations of 5%, 10%, 20%, and 40%, respectively. Conclusions: These results indicate that n-hexane and 70% ethanol extract from grape seeds have antibacterial potential against E. faecalis.